Ngaji Rasa in the Islamic Boarding School Curriculum and Its Implications for Islamic Religious Education: An Analysis from the Perspective of Kyai - Abu Warasy Batula; Agus Fakhruddin; Achmad Faqihuddin (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study examines the Ngaji Rasa curriculum in Islamic boarding schools and its implications for Islamic Religious Education (IRE) from the perspective of kyai, against the backdrop of moral degradation in formal education environments that indicates cognitively oriented approaches in IRE have been ineffective in internalizing moral and spiritual values. As an inner development-based educational practice, Ngaji Rasa offers an alternative model grounded in life experiences, behavioral exemplars, and habituation. Using a qualitative phenomenological design, the study involves ten kyai from traditional Islamic boarding schools, with data collected through in-depth interviews, participatory observation, and documentation analysis. The findings show that Ngaji Rasa operates as an unwritten hidden curriculum that significantly shapes students’ character formation through the exemplary conduct of the kyai, systematic habituation of values, and gradual spiritual experiences. This model contributes to fostering honesty, patience, humility, and social responsibility among students. The implications for Islamic Religious Education (PAI) include the development of experience-based learning, the strengthening of teacher role modeling, the cultivation of appropriate behavior, and the creation of a virtuous classroom atmosphere. Overall, this educational model bridges modern pedagogical theory with classical Islamic tradition, offering a holistic and transformative framework for religious education.